Commodity-driven integration of stock markets in Africa. Issue 11 (25th June 2017) - Peltomäki, Jarkko; Graham, Michael; Alagidede, Paul
ABSTRACT: This article examines stock market integration for commodity-dependent African countries. The analysis is carried out in two phases – first we adjust the respective national equity returns for changes in commodity prices and examine integration in the context of commodity-adjusted stock returns, and second we focus on integration associated with changes in commodity prices in a novel modelling framework. The results for this unexamined area of research are interesting: (a) African stock markets are not driven by more than one common component and (b) commodity-adjusted integration is significantly lower than nonadjusted integration. We discuss the implications of the results for index construction, modelling and diversification in the conclusions.